1996
DOI: 10.1007/bf01298955
|View full text |Cite
|
Sign up to set email alerts
|

The semidirect products of finite cyclic groups that areI-E groups

Abstract: Abstract. An I-E group is a group in which the endomorphism near-ring generated by the group's inner automorphisms equals the endomorphism near-ring generated by its endomorphisms. In this paper we shall completely determine the finite groups that are semidirect products of cyclic groups and are I-E groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In a second study with 0 and 25% WDGS (14), a significant difference with individual animals samples was observed only on I of 2 sampling days. In contrast to the above studies (13,14), data reported by Peterson et al (21) indicated that WDGS in cattle diets at levels of 0 to 5017v had no effect on the probability of finding E. co/i 0157:H7 in feces, but dietary levels of 20 and 30% WDGS were associated with fewer E. coli 0157: H7 at the terminal rectum relative to 0% WDGS in the diet. These authors did not observe significantly higher probabilities for E. coli 0157:H7 at the terminal rectum with 40 and 50% WDGS diets as compared with a 0% WDGS diet, but the authors did report large variations with these diets.…”
Section: Several Reports Have Been Published Regarding E Co/imentioning
confidence: 69%
“…In a second study with 0 and 25% WDGS (14), a significant difference with individual animals samples was observed only on I of 2 sampling days. In contrast to the above studies (13,14), data reported by Peterson et al (21) indicated that WDGS in cattle diets at levels of 0 to 5017v had no effect on the probability of finding E. co/i 0157:H7 in feces, but dietary levels of 20 and 30% WDGS were associated with fewer E. coli 0157: H7 at the terminal rectum relative to 0% WDGS in the diet. These authors did not observe significantly higher probabilities for E. coli 0157:H7 at the terminal rectum with 40 and 50% WDGS diets as compared with a 0% WDGS diet, but the authors did report large variations with these diets.…”
Section: Several Reports Have Been Published Regarding E Co/imentioning
confidence: 69%